2016
DOI: 10.1037/apl0000091
|View full text |Cite
|
Sign up to set email alerts
|

A profile of profiles: A meta-analysis of the nomological net of commitment profiles.

Abstract: Although the majority of empirical commitment research has adopted a variable-centered approach, the person-centered or profiles approach is gaining traction. One challenge in the commitment profiles literature is that names are attached to profiles based on the within-study comparison among profiles and their relative levels and shapes. Thus, it is possible that different studies name the same profiles differently or different profiles similarly because of the context of the other profiles in the study. A met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
74
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(91 citation statements)
references
References 100 publications
9
74
1
1
Order By: Relevance
“…It also tends to be less demanding with respect to interpretation and statistical power compared to modelling higher-way interactions between multiple commitments in a variable-centred (e.g., regression) approach Morin, 2016;Van Rossenberg, 2015). This approach has been applied to explore profiles of the TCM mindsets (e.g., Kabins, Xu, Bergman, Berry, & Willson, 2016;Meyer et al, 2012), and, profiles of commitments to multiple targets (e.g., Meyer, Morin, & Vandenberghe, 2015;Morin, Meyer, McInerney, Marsh, & Ganotice, 2015;Morin et al, 2011).…”
Section: (Anc)mentioning
confidence: 99%
“…It also tends to be less demanding with respect to interpretation and statistical power compared to modelling higher-way interactions between multiple commitments in a variable-centred (e.g., regression) approach Morin, 2016;Van Rossenberg, 2015). This approach has been applied to explore profiles of the TCM mindsets (e.g., Kabins, Xu, Bergman, Berry, & Willson, 2016;Meyer et al, 2012), and, profiles of commitments to multiple targets (e.g., Meyer, Morin, & Vandenberghe, 2015;Morin, Meyer, McInerney, Marsh, & Ganotice, 2015;Morin et al, 2011).…”
Section: (Anc)mentioning
confidence: 99%
“…This requires a program of research to document the construct validity of the profiles, including evidence of consistency in (a) the profiles that emerge across samples and conditions, and (b) the ways these profiles relate to other theoryrelevant variables (see Marsh, Lüdtke, Trautwein, & Morin, 2009;Morin et al, 2011). Such consistency is beginning to emerge across studies (Kabins et al, 2016;, across subsamples from the same population (Meyer, Kam, Goldenberg & Bremner, 2013), and within samples over time (Kam, Morin, Meyer, & Topolnytsky, 2016). In one of the most stringent tests of consistency to date, Kam et al (2016) found that the same profiles emerged prior to and during an organizational change.…”
mentioning
confidence: 99%
“…Still other profiles might be unique to our sample of students, and studies with other populations might identify profiles not found in our study. This combination of common and unique profiles across populations/samples has been observed in other domains (e.g., organizational commitment: see Kabins, Xu, Bergman, Berry, & Willson, 2016;. Identifying the full set of meaningful configurations of HEXACO profiles might require analyses with a very large and diverse sample (cf.…”
Section: Implications and Future Directionsmentioning
confidence: 78%
“…Identifying the full set of meaningful configurations of HEXACO profiles might require analyses with a very large and diverse sample (cf. Herzberg & Roth, 2006;Kabins et al, 2016). This would then allow for comparison of profiles obtained with samples drawn from more unique populations.…”
Section: Implications and Future Directionsmentioning
confidence: 99%